FAKTOR-FAKTOR YANG MEMPENGARUHI POLA SEBARAN PERUMAHAN DI KABUPATEN SLEMAN - , ADITYA OCTORIO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Human need for housing has increased, thereby reducing the availability of land. Those thing, encourage property developers build housing with invalid permissions. Sleman Regency is one of the locations that has the residential growth is very rapid and continued to increase. The objective of this research are: (1) to determine the distribution pattern of residental in Sleman, (2) to determine the factors that influence the distribution pattern in Sleman, and (3) to determine the suitability of the distribution of housing with the Urban Land use Plan of Sleman regency. The investigation of this research were encompass: firstly, collecting data that has been established by agency or corporation that related to housing issues. Secondly, examinating on the spread pattern of residential based on Sleman District Residential Distribution Map as basis for calculating nearest neighbourhood index. Finally, analyzing the correlation between independent variables (residental distribution index), againts dependent variable (population growth, population density, slope, roads, educational facilities, health facilities, and economic facilities) used regression statistic techniques. The results showed: (1) the distribution pattern of residential complexes in Sleman forming a pattern clustered, (2) according to analyses that employing statistic technique, it is known that the factors that most influence the distribution pattern of residental are population density, availability of facility accessibility and economic, and (3) there are 8 residential location that is not in accordance with the Urban Land use Plan 2011-2031